Modeling the carbon isotope signatures of methane and dissolved inorganic carbon to unravel mineralization pathways in boreal lake sediments. (15th May 2018) - Clayer, F.; Moritz, A.; Gélinas, Y.; Tessier, A.; Gobeil, C.
Abstract: Vertical profiles of the concentration and isotopic composition (δ 13 C) of methane (CH4 ) and dissolved inorganic carbon (DIC), as well as of ancillary parameters, were obtained in the top 25 cm of a sediment column in a seasonally anoxic basin from an oligotrophic boreal lake. Modeling the profiles of CH4 and DIC concentrations and those of their δ 13 C signatures with reaction-transport equations allowed us to determine the organic matter (OM) degradation rates according to various reactions and to constrain the in situ isotopic fractionation factors and diffusivity coefficients of CH4 and DIC. This exercise reveals inter alia that (i) CH4 production occurs below a depth of 5 cm, with the highest production rate between 5 and 7.5 cm depth, (ii) all CH4 is produced through hydrogenotrophy, and (iii) methanogenesis yields a production rate of CH4 about three times greater than that of DIC. This latter observation indicates either that fermentation of OM is not the exclusive source of H2 sustaining hydrogenotrophy, or that the commonly assumed model molecule CH2 O does not adequately represent the fermenting OM, since its fermentation yields identical rates of CH4 and DIC production. The porewater profiles of Fe and SO 4 2 - suggest that some H2 may be produced during the reoxidation of reduced sulfur by Fe(III), but the rate of H2 production via this process, if active, would be insignificant in comparison to that required to sustain the estimated rate of hydrogenotrophy. We deduce that the imbalance between CH4 and DIC production rates is rather due to the fermentation of organic substrates that are more reduced than CH2 O, i.e., having a negative average carbon oxidation state (COS). From the constraints on reaction rates and on fermentation pathways imposed by the δ 13 C data, we infer that the organic substrate fermenting between depths of 5 and 7.5 cm should have a COS of −1.87. We thus submit that CH4 is produced in the sediments of the seasonally anoxic basin of our boreal lake through hydrogenotrophy coupled to the fermentation of reduced organic substrates that can be represented by a mixture of fatty acids (e.g. C16 H32 O2 ; COS of −1.75) and fatty alcohols (e.g., C16 H34 O; COS of −2.00). This study emphasizes the importance of characterizing the sedimentary OM undergoing mineralization in order to improve diagenetic model predictions of CH4 cycling in boreal lakes and of its significance in climate change.